Purple loosestrife (Lythrum salicaria L.) in a southeastern sedge meadow - (:unkn) unknown (My University, 1989)
Floristic and seed bank composition of a sedge meadow containing purple loosestrife was examined in 1987 and 1988. Eleocharis spp., Spiraea tomentosa, Triadenum vircrinicum, and Lycopus spp. were widespread while infrequent or absent in nearby sedge meadows without purple loosestrife, suggesting that these species have similar microsite requirements. Changes noted in some species over time probably resulted from changes in climatic and soil moisture conditions. The seed bank reflected the dominant herbaceous vegetation but lacked a few species having moderate frequencies in the established vegetation. Limited samples, unsuitable germination conditions in the greenhouse, autumn seed germination by some species and inability to survive prolonged inundation may explain the paucity of seed of some species that were frequent in the vegetation. Herbicide treatment of above ground purple loosestrife tissue was effective but did not result in a decline in frequency/ probably because of resprouting. Areas with few individuals of purple loosestrife can be effectively managed by hand spraying individual plants and by removing flowering stalks at the time of herbicide treatment.
Keywords: Purple loosestrife; Lythrum salicaria L.; sedge meadow